Role of ADAMTS13, VWF and F8 genes in deep vein thrombosis. - Maria Teresa Pagliari (Public Library of Science (PLoS), 2021)
Background We previously described the association between rare ADAMTS13 single nucleotide variants (SNVs) and deep vein thrombosis (DVT). Moreover, DVT patients with at least one rare ADAMTS13 SNV had a lower ADAMTS13 activity than non-carriers. Aims To confirm ADAMTS13 variants association with DVT and reduced plasma ADAMTS13 activity levels in a larger population. To investigate the role of VWF and F8 variants. Methods ADAMTS13, VWF and F8 were sequenced using next-generation sequencing in 594 Italian DVT patients and 571 controls. Genetic association testing was performed using logistic regression and gene-based tests. The association between rare ADAMTS13 variants and the respective plasmatic activity, available for 365 cases and 292 controls, was determined using linear regression. All analyses were age-, sex- adjusted. Results We identified 48 low-frequency/common and 272 rare variants. Nine low-frequency/common variants had a P<0.05, but a false discovery rate between 0.06 and 0.24. Of them, 7 were found in ADAMTS13 (rs28641026, rs28503257, rs685523, rs3124768, rs3118667, rs739469, rs3124767; all protective) and 2 in VWF (rs1800382 [risk], rs7962217 [protective]). Rare ADAMTS13 variants were significantly associated with DVT using the burden, variable threshold (VT) and UNIQ (P<0.05), but not with C-ALPHA, SKAT and SKAT-O tests. Rare VWF and F8 variants were not associated with DVT. Carriers of rare ADAMTS13 variants had lower ADAMTS13 activity than non-carriers (ß -6.2, 95%CI -11,-1.5). This association was stronger for DVT patients than controls (ß -7.5, 95%CI -13.5,-1.5 vs. ß -2.9, 95%CI -10.4,4.5). Conclusions ADAMTS13 and VWF low-frequency/common variants mainly showed a protective effect, although their association with DVT was not confirmed. DVT patients carrying a rare ADAMTS13 variants had slightly reduced ADAMTS13 activity levels, but a higher DVT risk. Rare VWF and FVIII variants were not associated with DVT suggesting that other mechanisms are responsible for the high VWF and FVIII levels measured in DVT patients.